A case series of Humulin R U‐500 in insulin resistant people with type 2 diabetes. (2nd December 2021) - Dashora, Umesh; Ahmed, Suhail; Shaiq, Syed; Castro, Erwin; Khan, Shahid Ahmed; Bossman, Irene; Sathiskumar, Pariasamy
Abstract: Humulin R U‐500 has been in use worldwide but is not licensed in the UK. As it is five times concentrated, it has the potential to reduce the number of injections in patients requiring high doses. With the increasing use of U‐200 and U‐300 insulins, glucagon like peptide‐1 (GLP‐1) agonists, pioglitazone and sodium glucose co‐transporter2 (SGLT2) inhibitors, the role of U‐500 insulin is not clear. Ten patients with type 2 diabetes with a mean (SD) daily insulin requirement of 437.70 (112.75) units due to high mean (SD) BMI of 39.05 (4.92) were commenced on U‐500 insulin between November 2013 and August 2020. In this case series the effect on insulin dose, HbA1c, weight, hypoglycaemia and cost was investigated through a review of case notes. Results showed that after one year of treatment the mean (95% CI) HbA1c reduced by 14.5mmol/mol (2.23 to 26.77, p=0.02). Numerically, the mean (95% CI) insulin dose reduced by 57 units (‐36.13 to 150.53), body weight increased by 2.41kg (‐22.37 to 17.55). Self‐reported minor hypoglycaemia increased. There was no severe hypoglycaemia or hospital admission from hypoglycaemia. We calculated a cost saving of £366 per person per year of treatment. It was concluded the use of U‐500 continues to have a role in the management of the severely insulin resistant patient on existing glucose lowering therapy. There is an improvement in HbA1c for the majority of people. Weight gain and hypoglycaemia occurred as a side effect in some people as expected with potent insulin treatment. Copyright © 2021 John Wiley & Sons.